2003
DOI: 10.1097/00019606-200306000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Cell Detection in Peritoneal Washing: Cytology Versus RT-PCR for CEA Transcripts

Abstract: This study investigates the sensitivity and specificity of cytology, qualitative, and real-time RT-PCR methods in free cancer cell detection of peritoneal washing from gastric cancer patients. Peritoneal washings were collected from 65 gastric cancer patients for routine cytology and total RNA extraction for qualitative and real-time RT-PCR for CEA. The sensitivity and false-positive rate was 51.1%, 0% for cytology, 48.9% and 5% for qualitative RT-PCR for CEA, and 42.5% and 5% for real-time RT-PCR for CEA. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In patients with serosa involvement, peritoneal recurrence reaches 50% even if curative resections are performed 14,15 . Peritoneal recurrence develops from peritoneal free cancer cells originating from the primary lesion or metastatic lymph nodes [16][17][18] . It has been shown that patients with a gastric tumor involving the serosa or the lymph nodes have a high probability of producing peritoneal free cancer cells and developing peritoneal recurrence or carcinomatosis [5][6][7][8][9][10] .…”
Section: Resultsmentioning
confidence: 99%
“…In patients with serosa involvement, peritoneal recurrence reaches 50% even if curative resections are performed 14,15 . Peritoneal recurrence develops from peritoneal free cancer cells originating from the primary lesion or metastatic lymph nodes [16][17][18] . It has been shown that patients with a gastric tumor involving the serosa or the lymph nodes have a high probability of producing peritoneal free cancer cells and developing peritoneal recurrence or carcinomatosis [5][6][7][8][9][10] .…”
Section: Resultsmentioning
confidence: 99%
“…The findings indicate that a combination of cytology and immunocytochemistry increases the detection rate of cancer cells in peritoneal washes from gastric cancer patients [7][8][9]. The quantitative detection of CEA mRNA in peritoneal washes using molecular biology techniques is also well correlated with prognosis [14,17,18,27,28]; however, these methods are time-consuming and labor-intensive, limiting their application for routine use.…”
Section: Discussionmentioning
confidence: 98%
“…Kodera et al [16] clearly showed that the presence of carcinoembryonic antigen (CEA) mRNA in peritoneal washes correlates with survival and peritoneal recurrence. Many researchers have reported the usefulness of molecular biological techniques for the detection of CEA and/or other markers, such as cytokeratin (CK) 20 mRNA, in peritoneal washes by quantitative reverse-transcription PCR (QRT-PCR) [11,13,14,[16][17][18][19][20]. However, these molecular biological techniques do exhibit some disadvantages for routine use in general clinical laboratories because they are timeand labor-intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Although the precise mechanism driving peritoneal recurrence remains unclear, the presence of malignant cells in the peritoneum at the time of surgery can lead to peritoneal recurrence[60,61]. Therefore, examination of peritoneal fluids has emerged as an option for identifying patients who are at high risk for peritoneal recurrence after curative resection.…”
Section: Selected Population For Intraperitoneal Chemotherapymentioning
confidence: 99%